Philosophical synergetic approach to the study of old age phenomenon - SALIMULLINA, E. V; ILINA, M. S; VILDANOVA, E. M; MULLAGAYANOVA, G. S; DYACHENKO, L. I (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTToday synergetics is an interdisciplinary trend, exploring general patterns in various phenomena. Philosophical comprehension of old age as the final path of human development includes, first of all, the attitude of a person to the process of aging and to his/her own finiteness. The body is no longer able to fulfill all the functions and to meet the social requirements of mobility and general health due to the physiological changes, and the soul is “in the teeth of death” facing the necessity of addressing the existential problem of the meaning of life.RESUMENHoy la sinérgica es una tendencia interdisciplinaria, que explora patrones generales en varios fenómenos. La comprensión filosófica de la vejez como el camino final del desarrollo humano incluye, en primer lugar, la actitud de una persona hacia el proceso de envejecimiento y hacia su propia finitud. El cuerpo ya no puede cumplir con todas las funciones y cumplir con los requisitos sociales de movilidad y salud general debido a los cambios fisiológicos, y el alma está "en los dientes de la muerte" ante la necesidad de abordar el problema existencial del significado de vida.